Transplantation of marginal organs: immunological aspects and therapeutic perspectives in kidney transplantation - Noble, Johan; Jouve, Thomas; Malvezzi, Paolo; Süsal, Caner; Rostaing, Lionel (Frontiers in immunology, 2020)
Recent data from the World Population Prospects projects that by 2050, nearly all regions in the world will have a quarter or more of the population aged 60 and above. Chronic kidney disease (CKD) has a high global prevalence (around 13%) worldwide and the prevalence of CKD and end-stage kidney disease (ESKD) increase with age. Kidney transplantation remains the best therapeutic option for ESKD, offering a survival benefit in comparison with dialysis maintenance for most patients. This review focuses on immunological aspects of kidney transplantation in older patients and marginal donors i.e. 60 years or older deceased kidney donors or 50 to 59 years old deceased kidney donors with comorbidities.
Gesehen am 08.04.2020